ANALISIS URAIAN JABATAN BERDASARKAN SKKNI DI PT HUMA INDAH MEKAR PROVINSI LAMPUNG - Sahrul Ari Irawan (PT Naureen Digital Education, 2023)
Human resources in the company are employees of the company itself. Various implementation of existing activities is expected to increase employee compatibility, through the use of job desc. There are many companies whose employees are not optimal and know exactly what their competencies and job specifications are. The purpose of this study is to know the position analysis at PT Huma Indah Mekar and to know the benefits of position analysis at PT Huma Indah Mekar, Lampung Province. The method of this research is qualitative by carrying out field observations, interviews, and literature studies. The respondents of this study were employees at PT Huma Indah Mekar. The results of this study are job descriptions at PT Huma Indah Mekar with two implementation indicators by or guided by SKKNI (Indonesian National Work Competency Standards) No. 149 of 2020, namely: conducting job analysis and determining job descriptions. All of these indicators are directed in the formation of a job desc which presents job descriptions from: position identity, position structure, main functions of the position, job duties, job responsibilities and indicators, authority, job title relationship, and job job job position requirements.